Syntheses of Heterocycle-2,3-Fused Indoline and Azaindoline Derivatives - Nishi, Takahide; Mishima, Naoki; Kato, Haruna; Yamada, Koji (Synlett, 2021)
We describe a practical method for synthesizing heterocycle-2,3-fused indoline or azaindoline derivatives through haloetherification and cyclization. We applied this method in syntheses of six- to eight-membered heterocycle-2,3-fused indoline and azaindoline derivatives. These derivatives, which contain sp3-hybridized carbons, might be useful as new scaffolds in medicinal chemistry.
Keywords: haloetherification; indolines; azaindolines; morpholines; oxazepines; oxazocines